NEW ASPECTS OF INTERPRETATION OF INTERMEDIALITY (Journal of Contemporary Philology, 2021)
The subject of analysis in this study is the re-reading of the media convergences that appear in the 1960s of the last century, shown through the artwork Prune. Flat. (1965) by Robert Whitman. The intermediateity characteristic for this work occurs as a result of simultaneous performance and film projection, which in the process of overlapping and juxtaposition create a nexus of media specifics, which immanently belong to the separate disciplines. Their merging generates new media specificity, according to R. Konstelanetz, a medium of extended theater, and the re-reading aims to show that, expansion occurs as a communication and adialogue between different disciplines in a new art form, event, and as such could be read, not only as an extension of the theater, but also of the film. The study aims to show that this is an essential dialectical principle of shaping and structuring, through the application of the terms co-presence, disruptive mechanism, assembly, according to Bertolt Brecht. The co-relationship between media articulations exposes the boundaries of poetic determinism and ontological valence, determines the author’s voice and point of view (M. Ball), placing the conflict between the structural elements on a conceptual level (S. Eisenstein). The study goes through the genealogy of the process of structuring the work, covering a referential rhizome between the poetic act as an act of resistance according to G. Agamben and various theoretical intersections which through a deductive approach re-examine mediation as a formulation of the new aesthetic materiality.
Keywords: intermediality; film; theater; event; representation; remediation